Penerapan Pendekatan Matematika Realistik untuk Meningkatkan Kemampuan Operasi Hitung Perkalian - Sarniyati Yusmanita; M. Ikhsan; Cut Morina Zubainur (Universitas Hamzanwadi, 2018)
This research was conducted to know the activity, learning result, and student's response to learning using Realistic Mathematics Education (RME) approach on multiplication counting material. This research is a Classroom Action Research which carried out three cycles. The subjects were 33 fourth grade students of SD Negeri 46 Banda Aceh. Data collection was done by using formative test of student learning result, student activity observation sheet, and student response questionnaire. The results showed that the expected student activity in the learning process was improved by using RME approach on multiplication counting material in class IV SD Negeri 46 Banda Aceh. There are 40% of active student activity, the second cycle is 80% active student activity, and in 100% cycle 100% active student activity. Furthermore there is also an increase in the ability of student counting operations multiplication in each cycle. The cycle-I is 33.3% complete, the II-cycle is 63.6% complete, and the III-cycle is 96.97% complete. Student response is also very positive on the learning by using PMR approach on the material of multiplication operation in class IV SD Negeri 46 Banda Aceh.